THE DYNAMICS OF INTELLECTUAL CAPITAL IN RUSSIAN COMPANIES - Z. Mildzihov (Вестник университета, 2016)
In the article the author analyzes the intellectual capital of the largest Russian companies, which in modern conditions the main source of competitiveness. Considers such indicators as the ratio of the company's annual revenue to the value of its assets, as well as the size and dynamics of the intellectual capital of the organization. As the analysis shows, the few large Russian companies effectively use existing physical assets, and based on them, as well as intangible assets on the basis of creating a new economic value.